Specific proteolytic cleavage of recombinant Norwalk virus capsid protein. - Hardy, M E (1995)
Norwalk virus (NV) causes epidemic outbreaks of acute nonbacterial gastroenteritis in humans. The NV capsid is made up of a single protein, and expression of the capsid protein in baculovirus recombinants results in spontaneous assembly of the protein into virus-like particles (X. Jiang, M. Wang, D. Y. Graham, and M. K. Estes, J. Virol. 66:6527-6532, 1992). We have investigated whether the NV capsid protein undergoes a specific proteolytic cleavage. Recombinant NV (rNV) particles were digested with trypsin to determine if a specific cleavage occurred. A predominant band with a molecular weight of approximately 32,000 (32K protein) was observed when trypsin-treated rNV was electrophoresed on sodium dodecyl sulfate-polyacrylamide gels. Determination of the N-terminal sequence of this band showed that a trypsin-specific cleavage occurred at amino acid residue 227. Early studies identified two proteins with molecular weights of 59,000 and 30,000 (59K and 30K proteins) in the stool of NV-infected volunteers that were reactive with postinfection antiserum. (H. B. Greenberg, J. R. Valdesuso, A. R. Kalica, R. G. Wyatt, V. J. McAuliffe, A. Z. Kapikian, and R. M. Chanock, J. Virol. 37:994-999, 1981). We hypothesized that the 32K rNV cleavage product might be analogous to the 30K soluble protein detected in stools of NV-infected volunteers. Immunoprecipitation of soluble protein from these stool extracts with a rabbit polyclonal antiserum made against rNV, and Western blot detection with a mouse polyclonal antiserum made against rNV, revealed a single band with an apparent molecular weight of 30,000 that migrated similarly to the trypsin cleavage product observed in vitro. The N terminus of this band was identical to that of the 32K cleavage product of rNV capsid protein. These data show that the 30K protein in stool is produced by specific cleavage of the NV capsid protein in vivo. Trypsin cleavage of isolated soluble rNV 58K capsid protein and of assembled particles showed that only soluble 58K capsid protein is susceptible to cleavage. The presence of a large amount of soluble capsid protein may influence the immune response to or pathogenicity of NV infections.